Chemical process equipment selection and design - Couper, James R. (Amsterdam ; Boston : Elsevier, 2005)
Comprehensive and practical guide to the selection and design of a wide range of chemical process equipment. Emphasis is placed on real-world process design and performance of equipment. Provides examples of successful applications, with numerous drawings, graphs, and tables to show the functioning and performance of the equipment. Equipment rating forms and manufacturers' questionnaires are collected to illustrate the data essential to process design. Includes a chapter on equipment cost and addresses economic concerns. * Practical guide to the selection and design of a wide range of chemical process equipment. Examples of successful, real-world applications are provided. * Fully revised and updated with valuable shortcut methods, rules of thumb, and equipment rating forms and manufacturers' questionnaires have been collected to demonstrate the design process. Many line drawings, graphs, and tables illustrate performance data. * Chapter 19 has been expanded to cover new information on membrane separation. Approximately 100 worked examples are included. End of chapter references also are provided.
List of Examples; Rules of Thumb; Introduction; Flowsheets; Process Control; Drivers for Moving Equipment; Transfer of Solids; Flow of Fluids; Fluid Transport Equipment; Heat Transfer and Heat Exchangers; Dryers and Cooling Towers; Mixing and Agitation; Solid-Liquid Separation; Disintegration, Agglomeration, and Size Separation of Particulate Solids; Distillation and Gas Absorption; Extraction and Leaching; Adsorption and Ion Exchange; Crystallization from Solutions and Melts; Chemical Reactors; Process Vessels; Other Topics, Costs of Individual Equipment; Appendices; Index.
Includes bibliographical references and index.
Keywords: Chemical engineering -- Equipment and supplies; Chemical processes -- Equipment and supplies; Unit processes; Unit operations; Electronic books